Diagnostic Value of Stimulated Serum Thyroglobulin in the Follow-up of Patients with Differentiated Thyroid Cancer - Vlado Wagenhofer; Ivan Mihaljević; Tatjana Kralj; Dubravka Vrdoljak; Tomislav Kizivat (Acta Clinica Croatica)
The aim was to determine the diagnostic value of stimulated serum thyroglobulin (sTg) for the follow-up of patients with differentiated thyroid cancer (DTC) and to evaluate whether repeated sTg measurement provides additional clinical benefit in detecting persistent or recurrent structural disease if the initial sTg was negative. The retrospective study included 388 consecutive patients with DTC treated and followed-up between 2004 and 2018 at the Clinical Institute of Nuclear Medicine and Radiation Protection, Osijek University Hospital. The negative predictive value (NPV) of the first sTg measured 12 months after the initial treatment was compared with NPV of sTg measured annually during 3 consecutive years of follow-up. The first sTg NPV was 99.5% in the group of lowrisk patients and 96.1% in the group of intermediate-risk patients. In both low- and intermediate-risk groups, there were no differences between the first sTg NPV and NPV of sTg measured annually during 3 years of follow-up period. Repeated measurement of the sTg after initially negative result had a limited clinical value for detecting persistent or recurrent structural disease and cannot be recommended in routine follow-up of low- and intermediate-risk patients with DTC.